Development of an integrated ultrasonic membrane anaerobic system (IUMAS) for palm oil mill effluent (POME) treatment - N. H., Abdurahman; M. S., Hybat; Zulkifly, Jemaat; N. H., Azhary (Universiti Malaysia Pahang, 2018)
Biofouling is a critical issue in membrane water and wastewater treatment as it greatly compromises the efficiency of the treatment processes. It is difficult to control, and significant economic resources have been dedicated to the development of effective biofouling monitoring and control strategies. This manuscript introduces and investigates the potentials of an integrated ultrasonic membrane anaerobic system (IUMAS) as a single reactor unit to overcome membrane biofouling and retain the methane gas, CH4 in Pam oil mill effluent (POME) wastewater treatment. Six steady states were attained as a part of a kinetic study that considered concentration ranges of 11,760 to 18,400 mg/L for mixed liquor suspended solids (MLSS) and the mixed liquor volatile suspended solids (MLVSS) ranges from 9,000 to 16,008 mg/L. Steady state influent chemical oxygen demand, COD concentrations increased from 67,800 mg/L in the first steady to 82,700 mg/L in the sixth steady state. Kinetic equations from Monod, Contois, and Chen and Hashimoto were employed to describe the kinetics of POME treatment at organic loading rates ranging from 3 to 13 kg COD/m3/day. The chemical oxygen demand, COD removal efficiency was from 94% to 97% with hydraulic retention times, HRTs from 750 to 10 days. The methane gas yield production rate was between 0.21 and 0.55 l/g COD/day. The complete treatment reduced the COD content to 4,962 mg/L equivalent to a reduction of 94%.